Perubahan Arsitektur Pada Rumah Adat Kampung Kamanasa di Kabupaten Malaka, Kecamatan Malaka Tengah, Nusa Tenggara Timur - Putu Padma Sthri Meila Utami; I Putu Gede Laksmana Adisatya; Nyoman Ratih Prabandari; Ni Komang Indra Mahayani; Made Mas Surya Wiguna (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
This study identifies changes that have occurred in Archipelago Traditional Architecture, in this case taking a case study of Traditional Houses in Kamanasa Village, Central Malacca District, Central Malacca District. Data collection was carried out using field surveys and direct interviews with indigenous peoples in Kamanasa Village. The analysis was carried out by comparing and describing the differences that reflect changes in traditional house buildings in Kamanasa Village from an architectural point of view. Along with the times, traditional houses in Kamanasa Village have changed in terms of function, spatial planning, to construction and building materials. This architectural change was influenced by the growing needs of the community, practicality in the development process, to the increasingly limited availability of old materials and began to be replaced with new ones. This architectural change also creates differences between buildings that tend to be sacred or bound by customary rules and buildings where indigenous peoples live in general. The changes occur in spatial planning that adapts to the needs of the occupants' activities. This has implications for the appearance of buildings that seem more closed and private. The standards for health, safety and security for the occupants have also increased, so that traditional houses which function as residences usually have undergone a change in the use of materials that are easy to clean and the use of structures that are felt to be stronger and safer.